Biopori: Solusi Sampah Organik Untuk Kesuburan Tanah di Taman Toga Desa Sentul, Kec. Purwodadi, Kab. Pasuruan - Indrawati, Dwi Wahyu; Aprilia, Erika Putri; Anugraheni, Saskia Dwi; Firdaus, Alfiadny (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Sentul Village, Purwodadi District, Pasuruan Regency, has approximately 3,050 residents, with low household organic waste management practices. Improper waste management can increase environmental pollution risks and reduce the productivity of home gardens. This community service activity aimed to improve residents’ knowledge and skills in managing organic waste through the construction of biopore holes in the TOGA (Family Medicinal Plants) Garden. The activity was conducted from February 1 to 11, 2025, involving 50 housewives who collectively constructed 25 biopore holes as a natural composting medium. Evaluation was carried out by measuring the volume of organic waste before and after the activity, as well as pre–post tests using questionnaires to assess participants’ knowledge improvement. The results showed that the utilization of 25 biopore holes reduced the volume of household organic waste sent to the landfill by 30% and increased the average participants’ knowledge score from 62% to 85%. Furthermore, the compost produced enhanced the fertility of the TOGA Garden soil, indicated by improved growth of planted seedlings. In conclusion, the biopore method is an effective and sustainable solution for reducing household organic waste, increasing community knowledge, and improving environmental quality. This approach can be replicated more widely in other communities